A Review of Key Apparatus of Urban Rail Transit Full Automatic Operation System - LU Xiangyang; LYU Haojiong; LIAO Yun; GUO Rui; MA Weijie (机车电传动)
The technology diagram of key apparatus of urban rail transit full automatic operation system was presented. Some necessary improvements or enhancements for function or performance of the apparatus which included signal system ,rolling stock, ISCS, communication system , platform gate and so on were provided so as to fulfill the requirement of full automatic operation. At last, some problems should be focused on in design of the full automatic operation system were pointed out.